2020
DOI: 10.1111/lam.13393
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of alcohol‐based hand sanitizers against human norovirus using RNase‐RT‐qPCR with validation by human intestinal enteroid replication

Abstract: Significance and Impact of the Study: The purpose of this study was to evaluate the efficacy of two alcohol-based commercial hand sanitizers and 60% ethanol by suspension assay using RNase-RT-qPCR, with subsequent validation of efficacy by human norovirus (HuNoV) cultivation using stem cell-derived human intestinal enteroids (HIE). When HuNoV was treated with hand sanitizers, a 2Á2-3Á2 log 10 reduction was observed using RNase-RTqPCR. Adsorption to HIE was inefficient, and replication was nonexistent at 72 h p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…After a 60 s contact time, 10 μl of this solution was added to 90 μl of complete growth media with omitted growth factors (CMGF-) but supplemented with 10% fetal bovine serum for neutralization. Consistent with previous studies, a notreatment control (untreated virus stock) and a neutralization control (virus exposed to the neutralizer) were used (Costantini et al, 2018;Escudero-Abarca et al, 2020;Randazzo et al, 2020). Prior to infection of the HIEs, neutralized samples were purified using detergent removal spin columns (Thermofisher) to reduce residual cytotoxicity, as per ASTM E1482-12 (ASTM International, 2017).…”
Section: Ex Vivo Suspension Assays For Hnov Infectivitymentioning
confidence: 99%
“…After a 60 s contact time, 10 μl of this solution was added to 90 μl of complete growth media with omitted growth factors (CMGF-) but supplemented with 10% fetal bovine serum for neutralization. Consistent with previous studies, a notreatment control (untreated virus stock) and a neutralization control (virus exposed to the neutralizer) were used (Costantini et al, 2018;Escudero-Abarca et al, 2020;Randazzo et al, 2020). Prior to infection of the HIEs, neutralized samples were purified using detergent removal spin columns (Thermofisher) to reduce residual cytotoxicity, as per ASTM E1482-12 (ASTM International, 2017).…”
Section: Ex Vivo Suspension Assays For Hnov Infectivitymentioning
confidence: 99%
“…Compared to PBS treatment, EtOH 70% at two exposure times (30 s and 1 min) resulted in ≥99% reduction of infectivity of GII.4 Sydney[P31], GII.4_New Orleans[P4], and GII.3, while the infectivity of GII.4 Den Haag[P4], GII.17, and GI.1 after 30 s and 1 min EtOH 70% exposure resulted in reductions (86% and 90%, 83% and 87%, and 31% and 81%) of viral infectivity, respectively. Using the same HuNoV cultivation system, Escudero-Abarca et al (2020) reported the virucidal efficacy of an alcohol-based hand sanitizer against one GII.4 Sydney strain, where moderate reduction in infectivity was observed after 1 min of treatment with 60% EtOH ( 35 ). Costantini et al (2018) also showed that the exposure of GII.4 variants to 70% EtOH for 1 min or 5 min resulted in up to ∼80% reduction of infectivity, but complete virus inactivation was not achieved ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…In order to prevent misinterpretation of the real risk to consumers, the detection method should include some means of differentiating between infectious and non-infectious virions. This subject has been examined widely ( Nuanualsuwan and Cliver, 2002 ; Baert et al, 2008 ; Lamhoujeb et al, 2008 ; Parshionikar et al, 2010 ; Sánchez et al, 2012 ; Moreno et al, 2015 ; Zhang et al, 2019 ; Escudero-Abarca et al, 2020 ). Methods in development have been described in the literature, but none has been standardized to date.…”
Section: Discussionmentioning
confidence: 99%